Dampak Diversity Management pada Employees Engagement: Peran Organizational Trust dan Job Insecurity - Rizka Sahnindita; Dodi Ria Atmaja (MES Bogor, 2024)
Workforce diversity such as differences in ethnicity, gender, education, language and so on in an organization needs to be managed properly in order to be able to achieve the vision, mission and goals of the organization. Due to good Diversity Management, Organizational Trust will emerge thereby creating Employees Engagement, which can prevent Job Insecurity from occurring. The purpose of this study is to explore Diversity Management and Organizational Trust to achieve Employees Engagement in service companies in Jakarta that specialize in the banking, telecommunications, and building construction sectors. This research was conducted on 125 respondents and was obtained through a questionnaire distributed online in July 2023. In this quantitative study, researchers used primary data and the Partial Least Square-Structural Equation Modeling (PLS-SEM) research method with data processing and analysis using SmartPLS. The results of this study confirm that Diversity Management has no effect on Employees Engagement, Organizational Trust has a positive effect on Employees Engagement, Diversity Management has a negative effect on Job Insecurity, while the moderating effect of Leadership Style has no significant effect on Employees Engagement. This research is limited to service companies in Jakarta, further researchers can explore manufacturing or trading companies. Suggestions that can be submitted for future researchers are to be able to replace the Leadership Style variable with transactional and transformational Leadership Styles.